Modulation in Translation Process - Kartini Rahmatillah (Universitas Cokroaminoto Palopo, 2017)
Many aspects have to be observed by translators in order to make a good and equivalent translation. One of these is meaning, because it is the main goal translators must reach in their translation activity. The object of this preliminary research was on the modulation or the shifting of meaning in the process of translation. This preliminary research was qualitative naturalistic research. It used the samples of translation, both from Indonesian to English and from English to Indonesian. The words that needed modulation were classified, the patterns of the words were analyzed and finally conclusion was drawn. The source text were about social and religious affairs, i.e. the training module for companionship for victims of violence against women (VAW) and Section III Chapter 14 and Glossary of Teaching and Researching Translation (Hatim, 2001).The aims of this preliminary research were to find out (1) what kinds of pattern that are said to be modulated, and (2) whether each pattern, either from TSu or TSa carries the same or different meaning. The result from this preliminary research showed that each pattern, even though different between TSu and TSa carries the same meaning and the patterns that are modulated were the changing of passive in TSu to active in TSa and both passive in TSu and TSa.